1987
DOI: 10.1111/j.1432-1033.1987.tb10622.x
|View full text |Cite
|
Sign up to set email alerts
|

4,8-Anhydro-N-acetylneuraminic acid. Isolation from edible bird's nest and structure determination

Abstract: A new, sialic-acid-derived compound was isolated from the acid hydrolysate of edible bird's nest by ionexchange chromatography. Combined use of mass spectroscopy and 'H-and 13C-NMR spectroscopy established that it is the 4,g-anhydro derivative of N-acetylneuraminic acid and that in solutions it exists in two tautomeric forms.The formation of the new compound supports and earlier finding that in the glycoprotein of edible bird's nest at least a portion of N-acetylneuraminic acid is acetylated at HO-4.Recently w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
1

Year Published

1993
1993
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 24 publications
0
21
1
Order By: Relevance
“…Fragments A and B indicate the molecular mass of the sialic acid derivatives and thereby the type and the number of substituents. [63]; for EI MS data of permethylated Kdn, see ref. Fragment A is formed from the molecular ion by the elimination of a methyl group originating from a trimethylsilyl substituent in trimethylsilylated (0-acylated0-alkylated) N-acylneuraminic acid derivatives.…”
Section: 33mentioning
confidence: 99%
“…Fragments A and B indicate the molecular mass of the sialic acid derivatives and thereby the type and the number of substituents. [63]; for EI MS data of permethylated Kdn, see ref. Fragment A is formed from the molecular ion by the elimination of a methyl group originating from a trimethylsilyl substituent in trimethylsilylated (0-acylated0-alkylated) N-acylneuraminic acid derivatives.…”
Section: 33mentioning
confidence: 99%
“…Many studies have been carried out on the tonic effects of EBN, and it has been shown that EBN stimulates mitosis hormones and the growth factor for epidermal growth, resulting in repair of cells and stimulation of the immune system (Kong et al, 1987;Ng et al, 1986). Recently, several carbohydrate molecules, including new sialic acid-containing compounds and glycoconjugates, have been detected in EBN (Pozsgay et al, 1987;Reuter et al, 1989;Wieruszeski et al, 1987;Kakehi et al, 1994;Martin et al, 1977;Yu-Qin et al, 2000), but the importance of sialic acid residues in EBN is not clear.…”
Section: Introductionmentioning
confidence: 99%
“…They differ not only in the substituent on the amino group (acetyl or glycoloyl), but also in the number (up to three), position (4, 7, 8 and 9) and nature (acetyl, lactoyl and methyl) of substituents on the hydroxyl groups of neuraminic acid. A recent addition is 4,6-anhydro-N-acetylneuraminic, acid found in edible bird's nest substance [134]. It is generally stated that sialic acid is not found in insects; conclusive evidence has now been presented for its presence in Drosophila melanogaster through all stages of development [ 1401.…”
Section: Monosaccharide Constituentsmentioning
confidence: 99%